Manifestations of rhetorical condensation and its semantic impact in free poetry (Fadwa Touqan) as a model Poem (To the martyr Wael Zaatir) - Al-Tobi, Abdullah Mohmmed Hommod; Al-Drmaki, Mahmood Saed Saif (Journal of Arabic Language Sciences and Literature, 2025)
This research aims to study the manifestations of rhetorical condensation and its semantic effect in free verse by analyzing the poem “To the Martyr Wael Zaatir” by Fadwa Touqan. The research uses the descriptive analytical approach to study rhetorical condensation in the poem, focusing on repetition, metaphor, and simile. The results indicate that rhetorical condensation is the storage of the word or style of the meanings intended to be conveyed to the speaker and creates a strong semantic effect. Rhetorical condensation has played a role in expanding the scope of meanings presented to the recipient. Images represented by simile and metaphor have predominated in the poem, which in turn are a rhetorical and linguistic reserve that the speaker employs to influence the recipient. The research recommends studying rhetorical condensation in modern Arabic poetry, using it in education, and analyzing its effect on the reader.
Keywords: Rhetorical condensation; Free poetry; Semantics; Fadwa Touqan; Simile imagery; Metaphorical imagery